2010
DOI: 10.3171/2010.7.gks10864
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficients for evaluation of the response of brain tumors treated by Gamma Knife surgery

Abstract: Object Cellular density is a major factor for change in the apparent diffusion coefficient (ADC). The authors hypothesized that loss of tumor cells after Gamma Knife surgery (GKS) may alter the ADC value and used diffusion weighted MR imaging (DW imaging) to evaluate cellular changes in brain tumors to detect their treatment response and the efficacy of GKS. Methods In this paper the authors describe a prospective trial involving 86 patients harboring 38 solid or predominantly solid brain metastases, 30 menin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…ADC mapping has also proven to be helpful in treatment response evaluation in B-cell lymphoma, brain, lung and pancreatic breast cancer (24). Similar to a previous DWI study in GIST (15), our study showed comparatively low pre-treatment ADC mean_thr and higher post-treatment ADC mean_thr with significant differences in GIST lesions.…”
Section: Discussionsupporting
confidence: 87%
“…ADC mapping has also proven to be helpful in treatment response evaluation in B-cell lymphoma, brain, lung and pancreatic breast cancer (24). Similar to a previous DWI study in GIST (15), our study showed comparatively low pre-treatment ADC mean_thr and higher post-treatment ADC mean_thr with significant differences in GIST lesions.…”
Section: Discussionsupporting
confidence: 87%
“…Recent studies are generally focused on surgical planning, differential diagnosis of CPA tumors and post-operative facial nerve outcome [12,13,16]. In current study surgical results and facial nerve outcome were not assessed.…”
Section: Discussionmentioning
confidence: 97%
“…This makes DW-MRI a potential biomarker for early response to treatment. In addition, a positive association between therapy-induced elevation in ADC values and better clinical outcomes has been described in certain treatments [43,44]. A recent pilot study by Morgan et al [45] showed that DW-MRI has potential for monitoring patients with early prostate cancer who opt for active surveillance.…”
Section: Diffusion-weighted Magnetic Resonance Imagingmentioning
confidence: 97%